UNSTABLE FRAILTY: A FOCUS FOR END OF LIFE CARE. (11th November 2018) - Stow, D; Matthews, F; Hanratty, B
Abstract: Frailty is associated with an increased risk of mortality and has been proposed as an indicator of need for palliative or end of life care. Previous work has demonstrated that single time point measures of frailty are not useful for predicting individual risk of mortality. We used a frailty index (eFI) generated automatically in electronic health records, to investigate the association between different longitudinal frailty trajectories and risk of death. People age >75 who died in a one-year period (cases) were age, sex and practice matched to individuals with no record of death over the same period (controls). Monthly frailty scores were calculated for one year prior to death in cases and for the same period for controls. Latent growth mixture models were used to investigate longitudinal patterns of change and associated impact on mortality. We analysed data from 26, 298 cases and matched controls. Three distinct frailty trajectories were identified. Rapidly rising frailty (eFI = 0.011 per month on average from a mean baseline of 0.21) was associated with a substantial increase in mortality (OR 2.84 95%CI 2.34 - 3.45) for 2.2% of the sample, compared with the stable group (eFI=0.0001 per month from a group mean of 0.26) for 76.6% of the sample. The rapidly rising group experienced an initial sharp rise in eFI from a low baseline, followed by a plateau. This may be useful in clinical practice, enabling recognition of people at risk, and allowing time for palliative care intervention.